2012
DOI: 10.1021/ie201151p
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance of Lambda Cyhalothrin Microemulsion with Biodiesel as an Alternative Solvent

Abstract: This study investigates a lambda cyhalothrin 2.5% (w/w) microemulsion formulation, with biodiesel as an alternative solvent, as a potential pesticide delivery system for oil-soluble pesticide active ingredients (AIs). This study presents a pseudoternary phase diagram of the investigated system, at room temperature by titration, and the surfactant/cosurfactant mass ratios (S/C), the oil-to-surfactant/cosurfactant mass ratios (O/SC) and the optimum formulation. This study also investigates the continuous structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Studies have indicated that the control efficiency of pesticide microemulsions is superior to those of ordinary emulsions, wettable powders, and other pesticide formulations [16] , [17] . It has been reported that a microemulsion of λ-cyhalothrin possesses better performance and stability than its commercial formulation [18] . Similarly, a microemulsion of triadimefon displayed significantly better antifungal activity against R. solani AG1-IA, when compared to a 20% triadimefon emulsion [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the control efficiency of pesticide microemulsions is superior to those of ordinary emulsions, wettable powders, and other pesticide formulations [16] , [17] . It has been reported that a microemulsion of λ-cyhalothrin possesses better performance and stability than its commercial formulation [18] . Similarly, a microemulsion of triadimefon displayed significantly better antifungal activity against R. solani AG1-IA, when compared to a 20% triadimefon emulsion [17] .…”
Section: Introductionmentioning
confidence: 99%
“…5,37,44,45 Nowadays green microemulsions are already on the market. 32,42,43,46 Especially mono-alkyl esters made from renewable biological sources such as vegetable oils or animal fats have been investigated, and the physical properties of microemulsions with these compounds as the oil phase are of growing interest.…”
Section: Introductionmentioning
confidence: 99%
“…As early as in the 1960s, cuphea, with its vast diversity of fatty acids, 56,57 was proposed as a source of fatty acids with medium chain lengths. 58 In recent years, biodiesel has gained importance in a great number of research and industrial processes, for example as green solvents, [59][60][61] in cleaning and degreasing agents 62 or cleaning up of oil spills, 63 as polymerization solvents, 64 in pesticides 43,46,65 or as an alternative to organic solvents in liquid-liquid extractions 66 and last but not least as biofuels. Biodiesel based microemulsions have already been made and tested 41 and the produced bicontinuous microemulsion-fuels are effective fuels with low emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants are substances composed of hydrophilic and hydrophobic groups that can substantially reduce the surface tension of a solution [47]. In recent years, surfactants have commonly been mixed to further improve their performance by taking advantage of their synergistic effects [48].…”
Section: Complex Surfactantsmentioning
confidence: 99%